2009
DOI: 10.1007/s11274-009-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene cloning, expression and characterization of an α-galactosidase from Pedobacter nyackensis MJ11 CGMCC 2503 with potential as an aquatic feed additive

Abstract: A gene, aga-MJ11, encoding an a-galactosidase (EC 3.2.1.22) was cloned from Pedobacter nyackensis MJ11 CGMCC 2503, expressed in Escherichia coli, and biochemically characterized. The gene consisted of 2,163 nucleotides encoding a 720 amino acid-protein with a theoretical molecular weight of 82.6 kDa. The deduced amino acid sequence of Aga-MJ11 shared the highest identity of 51% to an a-galactosidase from Parabacteroides distasonis (YP_001301506), which belongs to glycoside hydrolase (GH) family 36. Purified re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
(52 reference statements)
0
7
0
1
Order By: Relevance
“…Sequencing and conceptual translation showed that Aga-BC7050 had high sequence similarity to other reported α-galactosidases of GH family 36. Aga-BC7050 also had identities of < 41% compared to the reported protease-resistant α-galactosidases RmGal36 (33%) [ 13 ], Aga-F75 (41%) [ 12 , 31 ], Aga-MJ11 (34%) [ 17 ], Aga-F78 (37%) [ 11 , 32 ], Aga-S27 (33%) [ 19 ], and AgaAJB13 (34%) [ 18 ]. This indicates that Aga-BC7050 represents a new protease-resistant α-galactosidase from B .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequencing and conceptual translation showed that Aga-BC7050 had high sequence similarity to other reported α-galactosidases of GH family 36. Aga-BC7050 also had identities of < 41% compared to the reported protease-resistant α-galactosidases RmGal36 (33%) [ 13 ], Aga-F75 (41%) [ 12 , 31 ], Aga-MJ11 (34%) [ 17 ], Aga-F78 (37%) [ 11 , 32 ], Aga-S27 (33%) [ 19 ], and AgaAJB13 (34%) [ 18 ]. This indicates that Aga-BC7050 represents a new protease-resistant α-galactosidase from B .…”
Section: Resultsmentioning
confidence: 99%
“…According to other reports, bacterial α-galactosidases with protease resistance were also isolated from Pedobacter nyackensis MJ11 [ 17 ], a new Sphingomonas strain [ 18 ], Streptomyces sp. S27 [ 19 ], and B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only four protease-resistant α-galactosidases have previously been reported (Table 2) [5][6][7]20]. However, these α-galactosidases show thermolability at 50 or 60°C and specific activities of <71 U/mg with or without protease treatments at 37 o C, whereas rAgaAJB13 exhibited a half-life of >60 min at 60 o C and specific activities of 225.0-256.5 U/mg (Table 2) [5][6][7]20]. Furthermore, low amino acids identities (<37%) were found between AgaAJB13 and the previously identified protease-resistant α-galactosidases (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Determined at pH 5.0 and 37 o C, the specific activities of the purified rAgaAJB13 towards substrates of 2 mM pNPG, 0.5% (w/v) melibiose and raffinose, and 1.0% (w/v) soybean meal and cottonseed meal were 225.0 ± 10.5, 221.2 ± 8.4, 1.7 ± 0.1, 6.9 ± 0.2, and 2.8 ± 0.2 U/mg, respectively. When assayed at pH 5.0 and 60 o C, the Sequence names are shown with accession numbers, except AgaAJB13, as follows: ACN78884, Pedobacter nyackensis MJ11 α-galactosidase with protease resistance [20]; ADK91095, Streptomyces sp. S27 α-galactosidase with protease resistance [7]; ACQ72829, Gibberella sp.…”
Section: Enzyme Characterizationmentioning
confidence: 99%